POLYGENIC VARIATION FOR MORPHOLOGICAL AND BIOCHEMICAL TRAITS OF BRINJAL GENOTYPES (Solanum melongena L.) AND ITS WILD RELATIVES - NISHA SHARMA; K. D. BHUTIA; RAJESH KUMAR; SITA KUMARI PRASAD; ANKITA DEBNATH; MALAY MARUT SHARMA (The Bioscan, 2020)
In present investigation, seventeen genotypes of brinjal and its wild relatives assessed for variability for fourteen traits. Significant differences were noticed for all the traits with maximum fruit yield per plant was observed in genotype VR-2 (777.60 g) which may be proved as promising genotype for commercial cultivation in an organic land Sikkim. High PCV and GCV was observed for almost all the traits indicating the wider genetic variability in the germplasm material. High heritability accompanied with high genetic advance as percent of mean respectively, were noticed for almost all traits including polyphenol (99.99%, 148.65%), average fruit weight (98.18 % and 88.20 %). length of fruit (94.55%, 90.62 %), fruit circumference (94. 80%, 59.57 %) and fruit yield per plant (94.44 % and 97.87 %). Fruit yield per plant showed significant positive correlation with average fruit weight (0.91 and 0.93 respectively) both at genotypic and phenotypic level indicate the importance of this character as yield attributing trait for the genetic improvement of yield. Average fruit weight showed highest positive direct effect (0.842 and 0.674) on fruit yield both at phenotypic and genotypic level suggesting that these traits may be improved through direct selection due to predominant additive gene action.